New recommended practices in concrete durability - Millar, David; Paul, Rodney (Journal of Asian Concrete Federation, 2017)
Prior to the 1970’s concrete was generally regarded by asset owners, designers, and contractors as a reliable construction material that provided long term durability with relatively little maintenance. Subsequently, premature deterioration of concrete structures, arising from changing cement characteristics, quality management, and a number of other factors, damaged this reputation. The durability of concrete structures is a complex and difficult issue to design and manage due to many variables. Whilst research into concrete durability continues, the knowledge on exposure significance, deterioration processes, materials properties and workmanship implications has developed significantly over the last 25 years. In this time new durability design practices have been developed, including durability modelling methods, and new methods of construction have been introduced. The Concrete Institute of Australia (CIA) Durability Technical Committee perceived a need for a broader review of durability requirements, and following extensive industry consultation, determined that a comprehensive and unified durability guidance was required. The concrete durability topics considered under this review include: planning, exposure classes, deemed to comply requirements, good practice, modelling reinforcement corrosion, cracks and crack control, and testing.